Making a case the practical roots of biblical law - Milstein, Sara J. 1978- (Oxford Oxford University Press USA - OSO, 2021)
cover -- Making a Case -- Copyright -- Dedication -- Contents -- List of Illustrations -- Acknowledgments -- Abbreviations -- Introduction -- 1. The Role of Legal Texts in Mesopotamian Scribal Education -- 2. Hebrew Legal Fictions and the Development of Deuteronomy -- 3. Echoes of Contracts in the Hebrew Legal Fictions -- 4. Exodus 21-​22: Old Law Collection or Scribal Exercise? -- 5. The Distinct Nature of "Biblical Law" -- Appendix -- Bibliography -- Index of Authors -- Index of Subjects.
"Outside of the Bible, all of the known Near Eastern law collections were produced in the 3rd-2nd millennia B.C.E., in cuneiform on clay tablets, and in major cities in Mesopotamia and in the Hittite Empire. None of the five major sites in Syria to have yielded cuneiform tablets has borne even a fragment of a law collection, despite the fact that several have yielded ample legal documentation. Excavations at Nuzi have turned up numerous legal documents, but again, no law collection. Even Egypt has not yielded a collection of laws. As such, the biblical texts that scholars regularly identify as law collections would represent the only "western," non-cuneiform expressions of the genre in the ancient Near East, produced by societies not known for their political clout, and separated in time from the "other" collections by centuries. Making a Case challenges the long-held notion that Israelite and Judahite scribes either made use of "old" law collections or set out to produce law collections in the Near Eastern sense of the genre. Rather, Sara Milstein proposes that what we call "biblical law" is closer in form and function to another, oft-neglected Mesopotamian genre: legal-pedagogical texts. In the course of their education, Mesopotamian scribes copied a variety of legal-oriented school texts: sample contracts, fictional cases, sequences of non-canonical law, and legal phrasebooks. When Exodus 20-23 and Deuteronomy 12-26 are viewed in the context of these legal-pedagogical texts from Mesopotamia, their practical roots in comparable (lost) legal exercises begin to emerge"--
Description based on publisher supplied metadata and other sources
Keywords: Bible - Criticism, interpretation, etc; To 1500; Jewish law-History-To 1500; Iraq-History-To 634; Jewish Law -- History -- To 1500; Electronic books; Jewish Law; Jewish law - Biblical teaching; Law - Mesopotamia; Contracts - Middle East - History - To 333 B.C; History; Iraq -- History -- To 634; Irak - Histoire - Jusqu'à 634; Iraq